Hydrogen-bonding induced abnormal microphase separation behavior of poly(ethylene oxide)-b-poly(tert-butyl acrylate-co-acrylic acid) block copolymers. (2nd September 2016) - Huang, Jie; Wang, Rui-Yang; Xu, Jun-Ting; Fan, Zhi-Qiang
Abstract: Hydrogen (H)-bonding interaction was introduced into a poly(ethylene oxide)- b -poly( tert -butyl acrylate) (PEO- b -P t BA) block copolymer (BCP) by partial hydrolysis of t BA units into acrylic acid (AA) ones, in order to compete with the segregation force between the PEO and P t BA blocks. It was found that, as the hydrolysis degree ( D hyd ) of the P t BA block increased, the structure of the PEO- b -P( t BA- co -AA) BCPs underwent the change from hexagonally packed cylindrical (HEX) into body-centered cubic spherical (BCC), then into HEX. The first HEX-to-BCC transition at lower D hyd arose from the enhanced compatibility between the PEO and P( t BA- co -AA) blocks induced by the H-bonding interaction. When a PEO- b -P( t BA- co -AA) BCP with a HEX structure was heated, the BCC-to-HEX order-order transition (OOT), which was opposed to that in the common BCPs with an upper critical ordering temperature (UCOT) phase diagram, could be achieved because the H-bonding interaction was weakened at higher temperature. The second BCC-to-HEX at higher D hyd was interpreted in terms of the enhanced chain rigidity and the chain arrangement approximately parallel to the microdomain interface induced by H-bonding interaction. The variation of the H-bonding interaction with temperature and the conformational change of the PEO block induced by H-bonding interaction were verified with FT-IR. Graphical abstract: Highlights: H-bonding interaction was introduced into block copolymers to compete with microphase separation. The inverse order-to-order transition was achieved. The effect of chain conformation induced by H-bonds on microphase separation was revealed.